1997
DOI: 10.1016/s0014-5793(97)00850-8
|View full text |Cite
|
Sign up to set email alerts
|

Protein splicing in the yeast Vma1 protozyme: evidence for an intramolecular reaction

Abstract: Protein splicing is an autocatalytic reaction of a single polypeptide in which a spliced intervening sequence is excised out and the two external regions are ligated with the peptide bond to yield two mature proteins. We examined the reaction mechanism using a folding-dependent in vitro protein splicing system. Protein splicing proceeds at an optimal pH of 7 and is an intramolecular reaction. The reaction is not inhibited by potential protease inhibitors, suggesting that its mechanism is different from those c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 16 publications
(44 reference statements)
0
21
0
Order By: Relevance
“…A third in vitro splicing system, also involving the Sce VMA intein, was developed by Anraku and coworkers (19) and is based on the fact that expression of fusion proteins containing this intein in E. coli led to the accumulation of unspliced precursor as inclusion bodies, which could be solubilized in 6 M guanidine hydrochloride and made to undergo protein splicing by dialysis. Preliminary mechanistic studies by using this experimental system demonstrated that protein splicing is an intramolecular process, which is resistant to protease inhibitors (20); however, a serious limitation of these studies is that the refolding process and protein splicing were not clearly separated.…”
Section: Resultsmentioning
confidence: 99%
“…A third in vitro splicing system, also involving the Sce VMA intein, was developed by Anraku and coworkers (19) and is based on the fact that expression of fusion proteins containing this intein in E. coli led to the accumulation of unspliced precursor as inclusion bodies, which could be solubilized in 6 M guanidine hydrochloride and made to undergo protein splicing by dialysis. Preliminary mechanistic studies by using this experimental system demonstrated that protein splicing is an intramolecular process, which is resistant to protease inhibitors (20); however, a serious limitation of these studies is that the refolding process and protein splicing were not clearly separated.…”
Section: Resultsmentioning
confidence: 99%
“…The protein splicing domain of the intein is formed from the regions Xanking the endonuclease domain and the two domains have little or no functional or structural overlap (Duan et al, 1997;Moure et al, 2002). The chemical steps in protein splicing that generate the processed VMA have been described (Chong et al, 1996;Kawasaki et al, 1997) and further structural studies have added to these data (Duan et al, 1997;Moure et al, 2002;Anraku et al, 2005). created artiWcial, splicing-competent, VMA mini-inteins by the deletion of the internal homing endonuclease region (motifs C, D, E and H) from the S. cerevisiae VMA intein.…”
Section: The Vma Intein Of Saccharomycetesmentioning
confidence: 99%
“…Protein splicing proceeds by an intramolecular pathway requiring no exogenous cofactors. [4,5] All of the information necessary for splicing resides within the intein polypeptide plus the first extein amino acid at the C-terminal splice junction.…”
Section: Introductionmentioning
confidence: 99%